BENEFICIAL EFFECTS OF ANTHOCYANINS ON NEUROCOGNITIVE FUNCTIONS: A SYSTEMATIC REVIEW - Suryantari, Sang Ayu Arta; Masnathasari, NM Ayu; Sugiritama, I Wayan; Linawati, NM; Widianti, IGA (MNJ (Malang Neurology Journal), 2025)
Background: Increased research interest in natural compounds from plant has been reported to show possible protective effects on neurocognitive function. Anthocyanins, a polyphenol widely present in many red-blue fruits or plants, has received the most attention in this regard. Objective: This study was conducted to reviews published literature of anthocyanins effect on cognitive outcomes according to PRISMA guideline. Methods: We systematically searched relevant data in PubMed, ScienceDirect, and Medline database published in January 2014 to December 2023. Results: Thirteen studies were reviewed consisting of animal studies (n=7) and human studies (n=6). In animal studies, the effects are particularly important for critical signaling pathways involved in the development of Parkinson's and Alzheimer’s disease. Six human studies found that consuming anthocyanins-rich foods improved either one or more cognitive outcomes with the most significant improvement across all tests associated with memory. Conclusion: The impact of anthocyanins on cognitive aspects in both animal and human studies shows substantial potential. Due to the methodological restrictions and variations among the studies, future study is needed to explore the underlying mechanism and validate these discoveries.